Who is exposed to gas prices? How gasoline prices affect automobile manufacturers and dealerships - Meghan R. Busse; Christopher R. Kittel; Florian Zettelmeyer (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2012)
Many consumers are keenly aware of gasoline prices, and consumer responses to gasoline prices have been well studied. In this paper, by contrast, we investigate how gasoline prices affect the automobile industry: manufacturers and dealerships. We estimate how changes in gasoline prices affect equilibrium prices and sales of both new and used vehicles of different fuel economies. We investigate the implications of these effects for individual auto manufacturers, taking into account differences in manufacturers' vehicle portfolios. We also investigate effects on manufacturers' affiliated dealership networks, including effects implied by the changes in used vehicle market outcomes.
Keywords: 330